SDL 2017 : model-driven engineering for future internet : 18th International SDL Forum, Budapest, Hungary, October 9-11, 2017, Proceedings /: model-driven engineering for future internet : 18th International SDL Forum, Budapest, Hungary, October 9-11, 2017, Proceedings. (2017) - Unknown
No abstract available